Perbandingan Implementasi Prinsip Good Corporate Governance pada Bank Konvensional dan Bank Syariah - Cantika Florentina Br Bangun; Nadya Ervina Saragih; Vira Yuniar; Juliana Nasution (MES Bogor, 2023)
In principle, the relationship between the bank and its customers are saving money in the bank based on the relationship of trust, so that each bank is required to have to continue to maintain the level of health. Solutions that can be taken by the banks, both conventional banks and Islamic banks, to maintain the existence and level of health is with the implementation of the principles of good corporate governance. Therefore, it is interesting to examine the comparison of implementation of the principles of good corporate govenance in conventional banks and Islamic banks. The method used in this study is a normative legal research. This research use approach legislation. The results showed that in essence, the implementation of the principles of good corporate governance in conventional banks and Islamic banks are the ‘same’, because it refers to the “Code of Good Corporate Govenance Indonesian Banking” issued by the National Committee on Governance (NGG). The fundamental difference lies in Islamic principles used by Islamic bans. In addition to guided and supervised by the Financial Services Authority as conventional banks, Islamic banks are also supervised by the National Sharia Board MUI and Sharia Supervisory Board who served in each Islamic bank. Keywords: The Principles of Good Corporate Governance